2021
DOI: 10.3390/plants10102028
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Phytosterol and Triterpenoid Production in Plant Hairy Root Cultures—Simultaneous Stimulation or Competition?

Abstract: Plant in vitro cultures, including hairy roots, can be applied for controlled production of valuable natural products, such as triterpenoids and sterols. These compounds originate from the common precursor squalene. Sterols and triterpenoids distinctly differ in their functions, and the 2,3-oxidosqualene cyclization step is often regarded as a branch point between primary and secondary (more aptly: general and specialized) metabolism. Considering the crucial role of phytosterols as membrane constituents, it ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…As it has been frequently reported for toxic metals and metalloids, high Cd concentrations in plants can alter metabolic processes and exert various effects at the physiological, morphological, and molecular levels, e.g., growth inhibition, nutrition imbalance, photosynthesis suppression, chlorosis, and ROS (reactive oxygen species) increase [ 21 , 22 ]. Various reports indicate that the composition of steroids and triterpenoids might be modified under stress conditions; however, detailed studies on such effects exerted after exposure to heavy metals are scarce [ 11 , 23 , 24 ]. The first reported studies on this phenomenon, performed either on algae or plants, demonstrated effects such as increased levels of cholesterol and a decrease in the ratio of 24-ethylcholest-5-en-3β-ol to 24-ethylcholesta-5,24(28) Z -dien-3β-ol, two major sterols occurring in the marine diatom Asterionella gracilis [ 25 ], or the increase of stigmasterol and sitosterol contents parallel to the decrease of isofucosterol and campesterol, as observed for rice ( Oryza sativa cv.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As it has been frequently reported for toxic metals and metalloids, high Cd concentrations in plants can alter metabolic processes and exert various effects at the physiological, morphological, and molecular levels, e.g., growth inhibition, nutrition imbalance, photosynthesis suppression, chlorosis, and ROS (reactive oxygen species) increase [ 21 , 22 ]. Various reports indicate that the composition of steroids and triterpenoids might be modified under stress conditions; however, detailed studies on such effects exerted after exposure to heavy metals are scarce [ 11 , 23 , 24 ]. The first reported studies on this phenomenon, performed either on algae or plants, demonstrated effects such as increased levels of cholesterol and a decrease in the ratio of 24-ethylcholest-5-en-3β-ol to 24-ethylcholesta-5,24(28) Z -dien-3β-ol, two major sterols occurring in the marine diatom Asterionella gracilis [ 25 ], or the increase of stigmasterol and sitosterol contents parallel to the decrease of isofucosterol and campesterol, as observed for rice ( Oryza sativa cv.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a previous study, the reported increase in the dry weight of mercury-treated algal cells appeared to be uncoupled from cell division [ 25 ]. Moreover, the inhibition of sterol biosynthesis, according to the “plant Cornelian dilemma” of the growth-defense trade-off [ 24 ], can significantly induce the biosynthesis of triterpenoids or other compounds excessively accumulating in cells under stress conditions…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sterols and triterpenoids distinctly differ in their functions, and therefore, they are commonly regarded as general and specialized metabolites, respectively [ 21 ]. Since both sterols and triterpenoids are synthesized as products of one common precursor, 2,3-oxidosqualene, the trials of stimulation of triterpenoid biosynthesis in plants and plant in vitro cultures including hairy roots often concern the problem of the possible competition [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plants’ acclimation to environmental changes, as well as defense strategies against biotic and abiotic stress factors, involve a complex metabolic remodeling triggered by signaling molecules such as jasmonic acid [ 1 , 2 ]. It is generally postulated that the reallocation of energy and metabolic resources drives the antagonism between plant growth and defense, resulting in pathway competition between general and specialized metabolism [ 3 , 4 ]. In the context of the growth-defense trade-off, the course of metabolic modifications of steroids and triterpenoids is particularly intriguing.…”
Section: Introductionmentioning
confidence: 99%